Cognitively bounded rational analyses and the crucial role of theories of subjective utility. (11th March 2020) - Lewis, Richard L.; Howes, Andrew
Abstract: We agree that combining rational analysis with cognitive bounds, what we previously introduced as Cognitively Bounded Rational Analysis, is a promising and under-used methodology in psychology. We further situate the framework in the literature, and highlight the important issue of a theory of subjective utility, which is not addressed sufficiently clearly in the framework or related previous work.